Engineering principles and process designs for phosphorus recovery as struvite: A comprehensive review - Nageshwari, Krishnamoorthy; Baishali, Dey; Yuwalee, Unpaprom; Rameshprabu, Ramaraj; Gaanty Pragas, Maniam; Natanamurugaraj, Govindan; Sivaraman, Jayaraman; Thirugnanam, Arunachalam; Balasubramanian, Paramasivan (Elsevier Ltd)
The rising population relies heavily on expensive phosphate (P) fertilizers for its agricultural productivity that qualms the national food security. Globally, there is a growing concern for the profound reliance on finite phosphorite reservoirs for commercial phosphate fertilizers’ qualitative and quantitative production. On the contrary, uncontrolled discharging of nutrient-rich wastewaters into natural streams, affecting the aquatic ecosystem. These critical situations have caused a scientific threat that has forced the researchers to explore other opportunities for the conservation of nutrient resources, recovery, and recycling. This review examines the nutrient recovery paradigms for struvite production by curtailing the nutrient gap between wastewater treatment and agricultural productivity. It comprehends the fundamental chemistry, thermodynamics, and factors influencing the struvite production process with its detailed mechanisms. Further, it deliberates the possible struvite engineering strategies, including process designs to enhance P recovery at the lab, pilot, and commercial scale. Also, it emphasizes the applications of nutrient-loaded struvite as a slow-release fertilizer and the challenges associated with economic feasibility and scaling up of the process in recent decades.